International Criminal Court Jurisdiction Against Human Rights Violations by Philippine President After Withdrawal from Rome Statute (Universitas Negeri Semarang, 2023)
Rodrigo Duterte who has ordered the police to execute drug addicts who do not want to be arrested. However, the assailant was still shot despite surrendering to arrest, the police on behalf of the anti-drug unit went to people's homes and did so because of the policy of